Does market turbulence moderate the impact of relationship competency on small retail firm’s performances - Wong, Kiong Kin *; Anjam, M.; Mughal, S. A.; Toh, Seong-Yuen * (2019)
It has been widely acknowledged that small businesses are contributing a lot in all developing countries. The existing researchers have widely acknowledged the positive impact of relationship competency on firm's performance. Whilst emerging markets for Small businesses in different emerging or developing contexts are different from developed countries. Thus, the impact of entrepreneurs’ relationship competency on firm’s performances varies across different cultures or contexts. The aim of the current study was to analyse the impact of relationship competency on four types of firms’ performances namely financial and non-financial performances, business growth, and firm’s performance compared with rival firms among retail Small businesses owned by Malaysian Chinese entrepreneurs under the moderating role of market turbulence. Composition Based View (CBV) and Strategic Contingency Theory (SCT) were the underpinning theories. Eight hypotheses were created based on proposed research model and standard instrument was used to collect the data. A total of 300 small business retail owners in Selangor, Malaysia participated in study through standard survey. The data were collected at one point of time across the sample population by using sampling techniques of non-probability. The collected data were analysed using SPSS software and PLS-SEM techniques. Findings revealed the positive and significant impact of relationship competency on non-financial performance and on firms’ performances relative to their competitor firms. Furthermore, the positive and significant moderating influence of market turbulence was also found for enhancing the impact of relationship competency on business growth. However, findings revealed no impact of relationship competency on financial performance and business growth. Moreover, results did not reveal any moderating influence of market turbulence for the impact of relationship competency on firm’s financial and firm’s non-financial performances as well as on performance relative to competitors.